2022
DOI: 10.1007/s10579-021-09569-x
|View full text |Cite
|
Sign up to set email alerts
|

Introducing the Gab Hate Corpus: defining and applying hate-based rhetoric to social media posts at scale

Abstract: Introducing the Gab Hate Corpus: Defining and applying hate-based rhetoric to social media posts at scale. Lang Resources & Evaluation (2022).

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 63 publications
0
19
0
Order By: Relevance
“…To simulate human feedback for the instance explanation, we leverage ground truth rationales for SST (Carton et al, 2020) as human feedback. For hate speech detection, we use STF (de Gibert et al, 2018) as the ID dataset, and HatEval (Barbieri et al, 2020), Gab Hate Corpus (GHC) (Kennedy et al, 2018) and Latent Hatred (ElSherief et al, 2021) for OOD datasets. To simulate human feedback for the task explanations, we leverage group identifiers (e.g., black, muslims) (Kennedy et al, 2020b) be discarded for determining whether the instance is hate or not.…”
Section: Methodsmentioning
confidence: 99%
“…To simulate human feedback for the instance explanation, we leverage ground truth rationales for SST (Carton et al, 2020) as human feedback. For hate speech detection, we use STF (de Gibert et al, 2018) as the ID dataset, and HatEval (Barbieri et al, 2020), Gab Hate Corpus (GHC) (Kennedy et al, 2018) and Latent Hatred (ElSherief et al, 2021) for OOD datasets. To simulate human feedback for the task explanations, we leverage group identifiers (e.g., black, muslims) (Kennedy et al, 2020b) be discarded for determining whether the instance is hate or not.…”
Section: Methodsmentioning
confidence: 99%
“…Our account relies on a sociological perspective that accentuates a social and cultural construction of the hateful rhetoric. As Kennedy et al [ 28 ] observed, “hate speech is fundamentally embedded within the existing cultural and social context in which it occurs”. Consequently, the weights assigned to each category of hatred and their temporal shifts that we focus on here might be largely context specific, reflecting political and cultural dynamics that are central to South Korea.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In scholarship on the subject, intergroup hatred is most often studied in conjunction with intergroup violence (e.g. ( 51 )); understanding hatred in language, though, requires understanding the myriad ways in which words can be used to accomplish the goals of intergroup hate ( 17 ). We specifically rely on three main operationalizations of outgroup hateful rhetoric: (i) language used to incite genocide ( 52 ) (ii) identity-based prejudicial language ( 53 ), and (iii) dehumanizing language ( 17 ).…”
Section: Overview Of the Present Researchmentioning
confidence: 99%
“…As long as a deeper understanding of why and how individuals and collectives use language for hateful purposes eludes us, a long-term solution to the problem will as well. Based on the idea that the language of hate must be understood in order to be mitigated ( 10 , 17–20 ), the present work aims to situate this usage of language in the broader context in which hate may be motivated, framed, explained, and called for: morality.…”
mentioning
confidence: 99%